Oxaliplatin-induced neuropathic pain in cancer: animal models and related research progress - Yuxin Jiang; Yuxin Jiang; Jie Shi; Wenping Wang; Haozhe Piao; Huini Yao; Jun Yu; Zhenzhu Zhai; Qian Liu; Ningxin Li; Jiaqing Fu; Yue Shen; et al. (Frontiers in Pharmacology)
Oxaliplatin, a third-generation platinum-based chemotherapeutic agent, has shown substantial efficacy in cancer treatment. However, its associated side effects, particularly chemotherapy-induced peripheral neuropathic pain (CIPNP), continue to challenge cancer survivors globally. Clinically, it frequently presents as numbness, coldness, and discomfort in the limbs and extremities. Duloxetine is advised for analgesic purposes. Despite its clinical relevance, both the application methods and the underlying mechanisms of oxaliplatin-induced CINP warrant further investigation. Consequently, more precise animal models are needed to explore the mechanisms and progression of this condition. This review consolidates recent advancements in rat and mouse models of oxaliplatin-induced CINP, with the aim of enhancing modeling success rates and developing models that more accurately mirror disease progression. Such models are essential for advancing clinical research and drug development.